Behavior of FRP-confined FRP spiral reinforced concrete square columns (FCFRCs) under axial compression. (January 2022) - Zhou, Jie-Kai; Lin, Wen-Kai; Guo, Shao-Xiong; Zeng, Jun-Jie; Bai, Yu-Lei
Abstract: Fiber-reinforced polymer (FRP) confinement has been demonstrated to be efficient in enhancing the deformation and strength capacities of concrete, while Polyethylene terephthalate (PET) FRP-confined concrete easily exhibits a strain-softening stress-strain behavior, especially for PET FRP-confined concrete in square columns. In this study, novel PET FRP-confined FRP spiral reinforced concrete square columns (FCFRSCs) are proposed. Capitalizing the benefits of internal FRP spiral reinforcement, the strain-softening behavior of PET FRP-confined concrete is expected to be alleviated, leading to excellent mechanical performance of the proposed square columns. The axial compressive behavior of FCFRSCs, as well as square concrete-filled PET FRP tube columns (CFFTs) and FRP reinforced concrete columns (FRCs) as reference columns, were investigated via experimentation. The experimental results show that the strain softening behavior of confined concrete in FCFRSCs has been substantially enhanced with the internal FRP reinforcement, confirming the viability of the system. The strain softening behavior of FRP-confined concrete after the first peak is prevented and a hardening behavior is achieved for concrete in FCFRSCs, especially when the GFRP spiral pitch is 30 mm. Highlights: Novel PET FRP-confined FRP spiral reinforced concrete square columns (FCFRSCs) are proposed. Strain softening behavior of PET FRP-confined concrete is alleviated by the internal FRP reinforcement. The concrete in FCFRSCs features elastic-strain hardening-softening-hardening four-segment behavior.